2018
DOI: 10.1007/s11356-018-1309-7
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of rare earth elements within waste rocks from the Montviel carbonatite deposit, Québec, Canada

Abstract: Several rare earth element (REE) mine projects around the world are currently at the feasibility stage. Unfortunately, few studies have evaluated the contamination potential of REE and their effects on the environment. In this project, the waste rocks from the carbonatites within the Montviel proterozoic alkaline intrusion (near Lebel-sur-Quévillon, Quebec, Canada) are assessed in this research. The mineralization is mainly constituted by light REE (LREE) fluorocarbonates (qaqarssukite-Ce, kukharenkoite-Ce), L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…Indeed, they are found in many ARD cases [142,143] but most REE deposits are within geological settings that are not prone to ARD generation, such as pegmatites, carbonatites, and peralkaline igneous deposits, as well as within placers and clays ( [144] and references therein). Upon their release in near-neutral mine waters, REE concentrations are mostly controlled by secondary precipitation and sorption phenomena (Section 2.4) [145][146][147][148]. However, significant knowledge gaps remain as to the fate of REE released from mine wastes.…”
Section: The Geochemistry Of Neutral Drainagementioning
confidence: 99%
“…Indeed, they are found in many ARD cases [142,143] but most REE deposits are within geological settings that are not prone to ARD generation, such as pegmatites, carbonatites, and peralkaline igneous deposits, as well as within placers and clays ( [144] and references therein). Upon their release in near-neutral mine waters, REE concentrations are mostly controlled by secondary precipitation and sorption phenomena (Section 2.4) [145][146][147][148]. However, significant knowledge gaps remain as to the fate of REE released from mine wastes.…”
Section: The Geochemistry Of Neutral Drainagementioning
confidence: 99%
“…Although some authors propose a magmatic origin for these elements and barite in other carbonatites (e.g., [70]), the textural evidence and the mineral association with quartz suggest a hydrothermal origin for them, as it was also suggested in Tchivira [25]. Other carbonatites worldwide, for instance, Italian carbonatites [56,57]; the Amba Dongar complex, India [71][72][73]; the occurrences from Sichuan Province, China [74][75][76]; or the Montviel deposit, Canada [77][78][79][80]; may display similar late REE mineral associations. This interpretation poses a problem since it is difficult to deduce how hydrothermal processes distribute REE minerals within carbonatite.…”
Section: Metallogenetic Potential Of the Monte Verde Carbonatitesmentioning
confidence: 99%
“…In addition, other authors showed that REE fractionation is promoted by an increase in pH [24,43,44]. Edahbi et al showed, using thermodynamic equilibrium calculations on the humidity cell leachate data, that REE concentrations decreased significantly (from 10 −8 to 10 −16 mg/L) when pH values increase from 2.6 to 10 [45].…”
Section: Geochemical Behaviormentioning
confidence: 99%
“…The weathering of the different lithologies within the Montviel deposit was studied in a previous study [45], where it was demonstrated that the REE-bearing carbonates from the Montviel deposit generates various elements (e.g., Ba, Sr, F, Th, and REE) in mine drainage waters. It is known that the carbonates dissolution is incomplete in near neutral conditions [47][48][49], and that the carbonate dissolution rates are lowest in alkaline and neutral conditions and increase in acid conditions [50,51].…”
Section: Geochemical Behavior Of Reementioning
confidence: 99%
See 1 more Smart Citation